Whey protein fractionation using Q-Sepharose anion exchange chromatography and SP-Sepharose cation exchange chromatography - Rabiatul Adawiyah, Sharom (2013)
In dairy industry, whey protein fractionation is an important process that requires an effective method to separate valuable proteins in bovine whey protein. Bovine whey protein can be divided into two components which are major protein and minor proteins. The major protein contains approximately 50% of β-lactoglobulin (β-Lg), 20% of α-lactalbumin (α-Lac), 10% of bovine serum albumin (BSA) and 10% of immunoglobulin (Ig). Cation exchange and anion exchange chromatography is one of advance separation techniques that can fractionate bovine whey protein. All negatively charged proteins in whey were bound simultaneously to an anion exchange column (Q-Sepharose), while all positively charged proteins in whey were bound to a cation exchange column (SP-Sepharose). Whey protein and buffer solution (pH 4 - pH 10) were prepared before run the experiment. The method is based on the use of an ionic column and salt gradient elution buffer (Buffer solution plus 1 M NaCl). The collected fractions were analyzing using SDS-PAGE to determine which fractions that contain protein component. By using UPLC the concentration of protein exists in the fraction had been determined. Protein fractionation at pH 7 gives the best result with highest concentration of protein recover by using Q-Sepharose. While, by using SP-Sepharose show pure β-Lg can be fractionate at pH 5.